Development of storytelling media to increase Civic education interest in elementary students - Maulidya Hasanah Damanik; Reh Bungana Br Perangin-angin; Yakobus Ndona; Sri Yunita (Inovasi Kurikulum, 2025)
Students' interest in learning about Pancasila Education remains low due to the abstract nature of the materials and a lack of engaging, contextual media. Meanwhile, the analysis revealed that students require learning tools that foster active engagement, relate to real-life experiences, and support concrete understanding of values. The Merdeka Curriculum encourages learning through narratives and experiential activities. This study aimed to develop a valid, practical, and effective digital interactive storytelling-based media to enhance the learning interest of fourth-grade students at SD Negeri 050690 Sawit Seberang. The research employed the Research and Development method, utilizing the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The product was created using Canva and validated by experts in content, media, and language. The results indicated a validity score of 93% and a practicality score of 92%. Learning outcomes showed an average posttest improvement of 27 points compared to the pretest. The media connects Pancasila values to meaningful stories and visual narratives, thereby supporting both emotional and cognitive engagement. The primary contribution of this study lies in providing adaptive and curriculum-relevant learning media that support character education and student motivation in elementary schools.   Abstrak Minat belajar peserta didik terhadap Pendidikan Pancasila masih tergolong rendah karena penyajian materi yang bersifat abstrak, tidak kontekstual, dan belum didukung oleh media yang interaktif. Sedangkan hasil analisis menunjukkan bahwa peserta didik membutuhkan media pembelajaran yang memfasilitasi keterlibatan aktif, pemahaman nilai secara konkret, serta relevansi dengan kehidupan sehari-hari. Kurikulum Merdeka pun mendorong pembelajaran berbasis narasi dan pengalaman personal. Oleh karena itu, penelitian ini bertujuan untuk mengembangkan media digital interaktif berbasis storytelling yang valid, praktis, dan efektif untuk meningkatkan minat belajar peserta didik kelas IV SD Negeri 050690 Sawit Seberang. Penelitian menggunakan metode Research and Development dengan model ADDIE yang mencakup lima tahap, yaitu analisis, desain, pengembangan, implementasi, dan evaluasi. Produk dikembangkan melalui Canva, divalidasi oleh ahli materi, media, dan bahasa. Hasil validasi menunjukkan kelayakan media sebesar 93% dan kepraktisan sebesar 92%. Penggunaan media dalam pembelajaran menghasilkan peningkatan skor posttest rata-rata sebesar 27 poin dari pretest awal. Media ini menghubungkan materi nilai-nilai Pancasila dengan alur cerita yang bermakna dan visualisasi menarik sehingga mendorong keterlibatan peserta didik secara emosional dan kognitif. Penelitian ini menghasilkan kontribusi konkret berupa media pembelajaran yang adaptif terhadap karakteristik peserta didik dan relevan dengan kebutuhan kurikulum, sehingga mampu memperkuat pembelajaran karakter di sekolah dasar. Kata Kunci: media digital; minat belajar; pendidikan Pancasila; storytelling interaktif